Isdaan integrating the public in an aquaculture research facility and fish landing center - Sarvida, John Emmanuel Y.; Sicam, Olivia G. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
The country, as the second largest archipelagic nation, relies much on marine resources in order to thrive. The fisheries sector is an important aspect of everyday Filipinos, as well as the economic well-being of the country. With issues such as overfishing and the lack of adequate facilities however, many fisherfolk suffer and the public as well, being primary consumers. Isdaan shall address these issues, and additionally become a development that serves as the gap between the fisheries sector and the public. Contextualizing the project, which will be located in Batangas City, an aquaculture research building grants fishermen access to a sustainable mean of fish harvesting, as well as the benchmark for new data and researches which may be used to benefit the Batangas aquaculture scene. This thesis shall create a more engaging method of public involvement to the fisheries sector, beyond simply being consumers.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Fisheries -- Philippines; Small-scale fisheries -- Philippines